Battery cell and method for producing a battery cell, battery device, energy storage device
Patent Information
- Application Number
- CN202610713284.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-22
AI Technical Summary
[0004]本申请提供一种电池单体及其制备方法、电池装置、储能装置,至少有利于抑制锂离子分布不均匀、锂枝晶生长等问题,从而提升电池单体的循环寿命和安全性
本申请的电池装置中,隔膜的改性聚氨酯中具有磺酸锂基团和羧基锂基团,改性聚氨酯中的磺酸锂和羧基锂协同作用,能够增强隔膜的亲液性与保液能力,也能够降低离子的迁移能垒,均匀锂离子流,因此电池单体中的锂离子分布不均、锂枝晶生长等问题能够得到很好地抑制,从而提升电池单体的循环寿命以及安全性能。
Smart Images

Figure CN122291866B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of energy storage technology, and in particular to a battery cell and its preparation method, a battery device, and an energy storage device. Background Technology
[0002] Lithium-ion batteries and similar battery cells have large capacity, long cycle life, and no memory effect, and are widely used in consumer electronics, automobiles, energy storage and other fields.
[0003] However, during operation, individual battery cells are prone to problems such as uneven lithium-ion distribution and lithium dendrite growth, which can affect the cycle life and safety of the battery. Summary of the Invention
[0004] This application provides a battery cell and its preparation method, battery device, and energy storage device, which at least helps to suppress problems such as uneven lithium-ion distribution and lithium dendrite growth, thereby improving the cycle life and safety of the battery cell.
[0005] The first aspect of this application provides a battery cell, including a cell assembly, the cell assembly including a negative electrode, a separator and a positive electrode stacked together; a housing, the cell assembly being located inside the housing; an electrolyte, the electrolyte being located inside the housing; the separator including a base film layer, at least one surface of the base film layer being provided with modified polyurethane, the main link of the modified polyurethane being branched with organolithium groups, the organolithium groups including lithium sulfonate groups and lithium carboxyl groups.
[0006] A second aspect of this application also provides a method for preparing a battery cell, comprising: obtaining a modified slurry, the modified slurry comprising modified polyurethane, the main link of the modified polyurethane being branched with organolithium groups, the organolithium groups comprising lithium sulfonate groups and lithium carboxyl groups; coating the modified slurry onto at least one surface of a base film layer, and curing the modified slurry to obtain a separator; obtaining a battery cell assembly, the battery cell assembly comprising a negative electrode, a separator and a positive electrode stacked together; and placing the battery cell assembly inside a housing to obtain a battery cell.
[0007] A third aspect of this application also provides a battery device, including a battery cell as described in the first aspect, or a battery cell manufactured by a method for manufacturing a battery cell as described in the second aspect, the battery device including one or more of a battery module, a battery pack, or a battery cluster.
[0008] The fourth aspect of this application also provides an energy storage device, including the battery device of the third aspect, the battery device being used to store electrical energy.
[0009] The technical solution provided in this application has at least the following advantages: In the battery device of this application, the modified polyurethane of the separator contains lithium sulfonate groups and lithium carboxyl groups. The synergistic effect of lithium sulfonate and lithium carboxyl in the modified polyurethane can enhance the hydrophilicity and liquid retention capacity of the separator, and also reduce the ion migration energy barrier and uniform lithium ion flow. Therefore, problems such as uneven lithium ion distribution and lithium dendrite growth in the battery cell can be well suppressed, thereby improving the cycle life and safety performance of the battery cell. Attached Figure Description
[0010] One or more embodiments are illustrated by way of example with corresponding pictures in the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the pictures in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional technology, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0011] Figure 1 This is a process flow diagram of the battery cell manufacturing process in the embodiments of this application; Figure 2 This is a schematic diagram of the overall structure of the battery device in the embodiments of this application; Figure 3 This is a schematic diagram of the disassembled battery device in an embodiment of this application.
[0012] Reference numerals: 10-box; 11-first part; 12-second part; 20-cell battery; 100-battery assembly. Detailed Implementation
[0013] As mentioned in the background technology, battery cells are prone to problems such as uneven lithium-ion distribution and lithium dendrite growth during operation. This is because the separator in a battery cell typically has a highly hydrophobic base film, making it difficult for the electrolyte to fully wet the separator. This results in insufficient interfacial compatibility of the separator, leading to problems such as uneven lithium-ion distribution and lithium dendrite growth within the battery cell. Although existing technologies modify the separator, the modification process is complex, costly, and uses environmentally unfriendly materials, making it difficult to balance high performance with the demands of large-scale production.
[0014] Based on this, the battery cell provided in this application has a simple and low-cost preparation process for the separator. Moreover, the modified polyurethane in the separator can effectively suppress problems such as uneven lithium-ion distribution and lithium dendrite growth, thereby improving the cycle life and safety performance of the battery cell.
[0015] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined. Similarly, "multiple sets" refers to two or more sets (including two sets), and "multiple pieces" refers to two or more pieces (including two pieces).
[0016] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0017] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent three cases: A exists, A and B exist simultaneously, and B exists. In addition, the character " / " in this document generally indicates that the related objects before and after it have an "or" relationship.
[0018] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential," etc., indicating orientation or positional relationships, are based on the orientation or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application. For example, if the device or element in the illustration is inverted, then the element described as "below," "under," "below," or "bottom" of other elements or features will be oriented "above" or "top" of other elements or features. Therefore, the term "below" may cover both above and below orientation depending on the context in which the term is used, which will be obvious to those skilled in the art. Materials may be oriented in other ways (e.g., rotated 90 degrees, inverted, flipped), and the spatial relative descriptive terms used herein may be interpreted accordingly.
[0019] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0020] In the description of embodiments of this application, the terms "about," "approximately," "roughly," or "about" for referring to a specific parameter include numerical values, and those skilled in the art will understand that the deviation from the numerical value is within the acceptable tolerance of the specific parameter. For example, "about" or "about" for a numerical value may include additional numerical values that are in the range of 90.0% to 110.0% of the numerical value, such as in the range of 95.0% to 105.0%, 97.5% to 102.5%, 99.0% to 101.0%, 99.5% to 100.5%, or 99.9% to 100.1%.
[0021] In the accompanying drawings corresponding to the embodiments of this application, the thickness and / or area of layers, films, panels, regions, etc., are enlarged for better understanding and ease of description. Throughout the specification, the same reference numerals denote the same elements. Furthermore, when describing a component as being "generally" formed on another component, it means that the component is not formed on the entire surface (or front surface) of the other component, nor is it formed on a portion of the edge of the entire surface.
[0022] In the description of embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and may be further included. When describing a component (such as a layer, film, region, or substrate) on or on the surface of another component, the component may be "directly" located on the surface of the other component, or there may be an intermediate component between the two components. Conversely, when describing a component on the surface of another component, or a component "directly" on another component, or a component surface on which another component is formed or disposed, it indicates that there is no intermediate component between the two components. For simplicity and clarity, various components may be drawn at any scale. In the drawings, some components may be omitted for simplicity.
[0023] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "component" is also intended to include the plural form unless the context clearly indicates otherwise.
[0024] The “components” mentioned above can refer to layers, membranes, regions, parts, plates, or structures, etc.
[0025] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.
[0026] This application provides a battery cell, including a cell assembly, a casing, and an electrolyte. The cell assembly and electrolyte are located within the casing. The cell assembly includes a negative electrode, a separator, and a positive electrode stacked together. The separator includes a base film layer, and at least one surface of the base film layer is provided with modified polyurethane. The main link of the modified polyurethane is a branched organolithium groups, including lithium sulfonate groups and lithium carboxyl groups.
[0027] In this application, the modified polyurethane matrix possesses excellent mechanical strength, elasticity, wear resistance, and chemical stability. It not only serves as an attachment site for organolithium compounds but also enhances the mechanical properties of the separator. The carboxyl lithium in the modified polyurethane exhibits good hydrophilic properties, enhancing the separator's affinity for the electrolyte and ensuring that the electrolyte within the separator does not easily dry out during battery cell cycling, thus contributing to the long-term cycling stability of the battery cell. Furthermore, the carboxyl lithium also possesses a degree of flexibility, facilitating the formation of a denser and more stable separator and improving the contact interface between the separator and the electrode. In the modified polyurethane, the sulfonate groups in the lithium sulfonate possess strong polarity and electron-withdrawing ability, effectively interacting with lithium ions to help them escape the binding of solvent molecules, promoting the dissociation of lithium salts and the desolventization of lithium ions, significantly reducing the energy barrier for lithium ion migration. Additionally, both lithium sulfonate and carboxyl lithium provide abundant lithium-ion exchange sites, accelerating lithium-ion transport and ensuring a uniform lithium-ion flow. Therefore, the synergistic effect of the carboxyl lithium and lithium sulfonate groups in the modified polyurethane can fully absorb the electrolyte during cycling, while promoting the rapid dissociation of lithium ions in the electrolyte and providing abundant transport sites for the dissociated lithium ions, reducing the transport energy barrier of lithium ions, thereby ensuring uniform distribution of lithium ions in the battery cell and making it less prone to the formation of lithium dendrites, thus improving the cycle performance and safety performance of the battery cell.
[0028] In some embodiments of this application, the modified polyurethane has a core-shell structure. The core of the modified polyurethane includes a main chain, and the shell of the modified polyurethane includes organolithium groups. A connecting group is disposed between the core and the shell. Since the organolithium groups are located on the surface, the core-shell structured modified polyurethane can be stably dispersed in the liquid phase, which helps to reduce the difficulty of preparation; it can better construct lithium-ion conduction channels; it can also improve the affinity between the separator and the electrolyte; in addition, the core-shell structured modified polyurethane also has good film-forming properties and adhesion, which can improve the bonding strength inside the separator and ensure that the separator is not easily decomposed and peeled off.
[0029] The linking groups in the core-shell structure help improve the stability of the core-shell structure and the lithium-ion transport performance. Linking groups are generally divided into a primary group and a secondary group. The primary group needs to ensure that the organic groups in the shell structure can be successfully grafted onto the polymer backbone; therefore, this part is usually a functional group formed after polymerization. The type of the primary group depends on the terminal groups of the polyurethane prepolymer during preparation, and is usually an amide bond. The secondary group needs to connect the organolithium group and the primary group. Furthermore, this application does not have any particular restrictions on the secondary group in the linking group; it generally includes aromatic groups, including at least one of phenyl, naphthyl, biphenyl, pyridyl, or pyrimidinyl groups. The type of secondary group is determined by the monomer corresponding to the organolithium group. This application will also provide a detailed description of the modified polyurethane with a core-shell structure in subsequent sections.
[0030] In some embodiments of this application, the molar ratio of lithium sulfonate groups to lithium carboxyl groups is 1:1 to 3:1; this further improves the ionic conductivity of the membrane; it also gives the membrane suitable hydrophilicity, preventing excessive water absorption and swelling; and it ensures that the modified polyurethane has better film-forming properties and coating mechanical strength. Furthermore, in some embodiments of this application, the functionality of the organolithium groups in the modified polyurethane is 4 to 6. This functionality refers to a single polymer chain and can be controlled during the preparation process by adjusting the molar ratio of the polyurethane prepolymer to the hydrophilic monomer.
[0031] This application does not have specific requirements regarding the molecular weight and content of the modified polyurethane, as long as it meets the purpose of this application. For example, in some embodiments of this application, the number average molecular weight of the modified polyurethane is 5,000 to 200,000, specifically 5,000, 8,000, 10,000, 20,000, 60,000, 80,000, 100,000, 140,000, 160,000, 180,000, 200,000, etc., or within a range consisting of any two of the above values. In some embodiments of this application, the content of the modified polyurethane is 1 g / m³. 2 ~5g / m 2 Specifically, it can be 1g / m 2 2g / m2 3g / m 2 4g / m 2 5g / m 2 The content is a one-sided content, or within the range of any two of the above values.
[0032] In the battery cell of this application, the base film layer in the separator typically serves as a substrate, preventing direct contact between the positive and negative electrodes and providing adhesion sites for the modified polyurethane. Therefore, this application does not impose any particular restrictions on the material and shape of the base film layer, as long as it meets the above objectives and does not significantly impair the effectiveness of this application. Typically, the base film layer can be a polyolefin or other electrolyte-stable materials, such as aromatic polyamides, polytetrafluoroethylene, polyethersulfone, etc. In some embodiments, the polyolefin is polyethylene (PE) or polypropylene (PP). These materials can be used alone or in any combination. Furthermore, in some embodiments of this application, the shape of the base film layer includes porous sheets or non-woven fabric-like materials with excellent liquid retention properties. Specifically, in the embodiments of this application, a commercial polypropylene microporous membrane (20 μm thickness, 45% porosity) is uniformly used as the base film layer, which is vacuum-dried at 60°C for 12 hours before use to remove residual moisture.
[0033] This application does not have specific requirements for the total thickness of the separator, as long as it meets the purpose of this application. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator is within the above ranges, insulation and mechanical strength can be ensured, as well as the rate characteristics and energy density of the secondary battery.
[0034] In addition to the separator, the battery cell assembly also includes a positive electrode and a negative electrode. This application does not impose specific limitations on the positive and negative electrodes, as long as they meet the purpose of this application. As an example, this application provides the structure and materials of the positive and negative electrodes, which will be described in detail below.
[0035] The positive electrode includes a positive current collector and a positive active layer disposed on at least one surface of the positive current collector. Specifically, in this application, the positive active layer can be disposed on one surface or on two surfaces along the thickness direction of the positive current collector. Furthermore, in this application, the "surface of the positive current collector" can be the entire area of the positive current collector or only a portion thereof; there are no particular limitations, as long as the purpose of this application is achieved.
[0036] The positive electrode active layer comprises a positive electrode active material, which can be any material capable of reversibly inserting and de-intercalating Li. + Na +Substances containing alkali metal ions are used to ensure the normal charging and discharging of secondary batteries. For example, the positive electrode active material includes lithium salts, which can be lithium-containing phosphates. Lithium-containing phosphates refer to phosphate materials containing lithium elements and can be detected by any method known in the art. For example, detection can be performed using a combination of X-ray diffraction and energy dispersive spectroscopy, or inductively coupled plasma mass spectrometry. As examples, lithium-containing phosphates include, but are not limited to, at least one of lithium iron phosphate, lithium iron phosphate doped and modified materials, lithium iron phosphate coated and modified materials, lithium manganese phosphate, or lithium manganese iron phosphate. Lithium manganese iron phosphate, as an emerging high-voltage phosphate material, combines safety and high-voltage characteristics.
[0037] For example, the positive electrode active material can also be a high-voltage system with a working voltage greater than or equal to 4.3V, such as high-nickel ternary materials, high-voltage spinel materials, or lithium-rich manganese-based materials.
[0038] For example, high-nickel ternary materials such as LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.15 Al 0.05 O2 (NCA) and other compounds possess operating voltages of 4.3V~4.6V and high specific capacity, making them ideal cathode choices for high-voltage lithium metal batteries. High-voltage spinel LiNi... 0.5 Mn 1.5 O4 can operate at a voltage of up to 4.7V, matching its high voltage stability.
[0039] However, this application is not limited to the materials listed above, and other materials that can be used as positive electrode active materials in battery cells may also be used. These positive electrode active materials may be used alone, or two or more may be used in combination.
[0040] In some embodiments, the positive electrode active layer further includes a positive electrode conductive agent; this application does not limit the type of positive electrode conductive agent, and any known conductive material can be used. Specifically, the positive electrode conductive agent includes, but is not limited to, at least one of the following: acetylene black, Super-P carbon black, amorphous carbon such as needle coke, carbon nanotubes, or graphene.
[0041] In some embodiments, the positive electrode active layer generally also contains a positive electrode binder. There are no particular restrictions on the type of positive electrode binder used in the manufacture of the positive electrode active layer. In the case of the coating method, any material that can be dissolved or dispersed in the liquid medium used in the electrode manufacturing process is acceptable. Positive electrode binders include, but are not limited to, any one or at least two of the following: resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber-like polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; thermoplastic elastomers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers (EPDM), styrene-ethylene-butadiene-ethylene copolymers, and styrene-isoprene-styrene block copolymers or their hydrides; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorinated polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; and polymer compositions with ion conductivity of alkali metal ions (especially lithium ions).
[0042] In the positive electrode, there are no particular restrictions on the type of positive electrode current collector; it can be any known material suitable for use as a positive electrode current collector. The positive electrode current collector can be a metal foil or a composite current collector. For example, the metal foil may include, but is not limited to, aluminum foil. The composite current collector may include a base layer and a metal layer located on at least one surface of the base layer. For example, the base layer can be a polymer material base layer, including but not limited to polypropylene (PP) base layer, polyethylene terephthalate (PET) base layer, polybutylene terephthalate (PBT) base layer, polystyrene (PS) base layer, or polyethylene (PE) base layer. The material of the metal layer may include, but is not limited to, aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, or silver alloy. Furthermore, to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode active layer, a conductive additive or conductive coating may be provided on the surface of the positive electrode current collector. Conductive additives include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. The conductive coating may be a mixture of inorganic oxides, conductive agents, and positive electrode binders.
[0043] In preparing the positive electrode, it can be either formulated into a positive electrode slurry, coated onto a positive electrode current collector, and dried to form a positive electrode active layer on the current collector, thus obtaining the positive electrode; or the components in the positive electrode active layer can be dry-mixed, formed into a sheet, and then pressed onto the positive electrode current collector to form the positive electrode active layer, thus obtaining the positive electrode. When using this method to prepare the positive electrode, there are no particular restrictions on the solvent in the positive electrode slurry, as long as it can dissolve or disperse the aforementioned components. Specifically, the solvent in the positive electrode slurry includes, but is not limited to, N-methylpyrrolidone (NMP) and ethylene carbonate (EC).
[0044] The negative electrode includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, wherein the composition of the negative electrode active layer includes a negative electrode active material. That is, in this application, the negative electrode active layer can be disposed on one surface or on two surfaces in the thickness direction of the negative electrode current collector. Furthermore, in this application, the "surface of the negative electrode current collector" can be the entire area of the negative electrode current collector or only a portion thereof; there are no particular limitations, as long as the purpose of this application is achieved.
[0045] The negative electrode active layer generally contains a negative electrode active material, and this application does not impose any particular limitation on the negative electrode active material. Specifically, the negative electrode active material can be any negative electrode active material known in the art for use in battery cells. As an example, the negative electrode active material can be at least one of the following materials, including but not limited to: graphite, carbon materials, silicon-based materials, tin-based materials, or lithium titanate. Graphite can be artificial graphite or natural graphite. Carbon materials can be soft carbon or hard carbon. Silicon-based materials can be selected from at least one of elemental silicon, silicon-oxygen composites, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other materials that can be used as negative electrode active materials for battery cells can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0046] In some embodiments, the negative electrode active layer typically also contains a negative electrode conductive agent. This application does not particularly limit the type of negative electrode conductive agent, as long as it achieves the purpose of this application. For example, negative electrode conductive agents include, but are not limited to, at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon black, or graphene.
[0047] In some embodiments, the negative electrode active layer may also contain a negative electrode binder and a thickener. This application does not particularly limit the types of negative electrode binders and thickeners, as long as they can achieve the purpose of this application. For example, the negative electrode binder may include, but is not limited to, at least one of polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, or acrylated styrene-butadiene rubber; the thickener in the negative electrode slurry may include, but is not limited to, at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.
[0048] In the negative electrode, the negative electrode current collector can be a metal foil or a composite current collector. For example, the metal foil may include, but is not limited to, copper foil, and this application is not particularly limited. The composite current collector may include a base layer and a metal layer located on at least one surface of the base layer. For example, the base layer may be a polymer material base layer, including but not limited to polypropylene (PP) base layer, polyethylene terephthalate (PET) base layer, polybutylene terephthalate (PBT) base layer, polystyrene (PS) base layer, or polyethylene (PE) base layer. The material of the metal layer may include, but is not limited to, at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, or silver alloy.
[0049] Furthermore, in this application, there are no particular limitations on the thickness of the negative electrode current collector and the negative electrode active layer, as long as the purpose of this application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode active layer is 30μm to 160μm.
[0050] In preparing the negative electrode, the components of the aforementioned negative electrode active layer can be dissolved or dispersed in a liquid solvent to form a negative electrode slurry. This slurry is then coated onto a negative electrode current collector and dried to form a negative electrode active layer, thus obtaining the negative electrode. Alternatively, the components of the negative electrode active layer can be dry-mixed to form a sheet, which is then pressed onto the negative electrode current collector to form the negative electrode active layer, thereby obtaining the negative electrode. Furthermore, when the negative electrode of this application has a first active layer and a second active layer, a layered preparation method can be used, first preparing the first active layer and then preparing the second active layer. The solvent in the negative electrode slurry includes any one of aqueous solvents and organic solvents. Aqueous solvents include, but are not limited to, mixtures of alcohol and water or water itself. Organic solvents include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; and aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide. In some other embodiments, when using aqueous solvents, the negative electrode slurry composition may also include a thickener and styrene-butadiene rubber (SBR) emulsion to slurry the negative electrode slurry, thereby adjusting its viscosity. The types of thickeners in the positive electrode slurry include, but are not limited to, at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and their salts.
[0051] In a battery cell, the electrolyte is used to transport ions, enabling the cell to function properly. This application does not have specific requirements for the electrolyte, as long as it meets the objectives of this application. Typically, electrolyte components include lithium salts, organic solvents, additives, etc. As an example, a detailed description follows.
[0052] In some embodiments of this application, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide [LiN(SO2F)2], lithium bis(trifluoromethanesulfonyl)imide [LiNH(SO2CF3)2], lithium trifluoromethanesulfonate (LiCF3SO3), lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorodioxalate phosphate (LiODFP), and lithium tetrafluorooxalate phosphate (LiOTFP). This application does not impose any particular limitation on the content of the electrolyte salt in the electrolyte, as long as the purpose of this application is achieved. For example, based on the mass of the electrolyte, the mass percentage content of the lithium salt is 8% to 15%.
[0053] This application does not impose any particular limitation on organic solvents, as long as they achieve the purpose of this application. For example, organic solvents may include, but are not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents. The aforementioned carbonate compounds may include, but are not limited to, at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorocarbonate compounds. The aforementioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or methyl ethyl carbonate (EMC). The aforementioned cyclic carbonates may include, but are not limited to, at least one of ethylene carbonate (EC), butylene carbonate (BC), or vinyl ethylene carbonate (VEC). Fluorocarbonate compounds may include, but are not limited to, at least one of fluoroethylene carbonate, fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The aforementioned carboxylic acid ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valproic acid lactone, or caprolactone. The aforementioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. Other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate. This application does not impose any particular limitation on the solvent content in the electrolyte, as long as the purpose of this application is achieved.
[0054] In this application, the electrolyte may also include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain properties of the battery cell, such as additives that improve the overcharge performance of the battery cell, additives that improve the high-temperature or low-temperature performance of the battery cell, etc.
[0055] Accordingly, another embodiment of this application also provides a method for preparing a battery cell, which can be used to manufacture the battery cell provided in the above embodiments, and its preparation process flow diagram is shown below. Figure 1As shown in the accompanying drawings, the manufacturing method of a battery cell according to another embodiment of this application will be described in detail below. For parts that are the same as or corresponding to the previous embodiment, please refer to the corresponding description of the foregoing embodiment, which will not be described in detail below.
[0056] The method for preparing the battery cell of this application includes the following steps: S100. Obtain a modified slurry, the modified slurry comprising modified polyurethane, the main link of the modified polyurethane being an organolithium group, the organolithium group comprising lithium sulfonate group and lithium carboxyl group.
[0057] In this step, the modified polyurethane in the modified slurry can be commercially available or prepared in-house. As an example, this application provides a method for preparing the modified polyurethane, as follows: S110. Obtain the oil phase, which includes polyurethane prepolymer.
[0058] Polyurethane prepolymer (Pre-PU) is a high molecular polymer formed from polyether or polyester polyol and polyisocyanate. Pre-PU is a semi-finished polymer with controllable reactivity and can be used as a raw material for polyurethane.
[0059] The polyurethane prepolymer contains functional groups at its ends capable of condensation reactions, ensuring that the polyurethane prepolymer can subsequently polymerize to form polyurethane. For example, the ends may have isocyanate groups, hydroxyl groups, or blocked groups, etc., and this application is not limited in this regard. However, when the end groups are different, the polarity of other reactive groups of the raw materials will be adjusted accordingly. As an example, in the embodiments of this application, the end groups of the polyurethane prepolymer are isocyanate groups.
[0060] Similarly, polyurethane prepolymers can be commercially available or prepared in-house. In the preparation of polyurethane prepolymers, polyethers or polyester polyols, and polyisocyanates, can be selected according to actual needs, and this application does not impose any particular restrictions. For example, polyester polyols include, but are not limited to, at least one of polytetrahydrofuran ether diol and polycaprolactone diol. Polyisocyanates include, but are not limited to, at least one of 4,4'-diphenylmethanediisocyanate (MDI, CAS No. 101-68-8), toluene-2,4-diisocyanate (TDI, CAS No. 584-84-9), and isophorone diisocyanate (IPDI, CAS No. 4098-71-9).
[0061] S120. Obtain an aqueous phase, which includes hydrophilic monomers and chain extenders. The hydrophilic monomers include lithium sulfonate salts and lithium carboxyl salts, and the hydrophilic monomers contain polymeric groups.
[0062] In this step, the hydrophilic monomer in the aqueous phase can provide lithium sulfonate and lithium carboxyl groups, as well as polymeric groups. These polymeric groups ensure that the hydrophilic monomer can react with the polyurethane prepolymer. Therefore, the polymeric group reacts with the terminal groups of the polyurethane prepolymer to form the first linking group. The portion of the hydrophilic monomer that simultaneously links the first group and the organolithium group is the second linking group. In this step, the type of polymeric group is determined by the terminal groups of the polyurethane prepolymer. Since the terminal group of the Pre-PU in this application is isocyanate, the polymeric group in the hydrophilic monomer is generally amino.
[0063] In addition, chain extenders in the aqueous phase can increase the degree of polymerization, which can be controlled according to actual needs.
[0064] S130. The oil phase and the water phase are mixed and subjected to a polymerization reaction to obtain modified polyurethane.
[0065] In this step, after the oil and aqueous phases are mixed, the polyurethane prepolymers polymerize through a chain extender, and the polyurethane prepolymers also react with hydrophilic groups to obtain modified polyurethane. During the reaction, the lithium sulfonate and lithium carboxyl groups in the molecular chain endow the product with strong hydrophilicity, enabling the modified polyurethane to self-assemble in situ in the aqueous phase to form particles with a core-shell structure and uniform size.
[0066] In some embodiments of this application, the mass ratio of the oil phase to the water phase during the polymerization reaction is generally 1:2 to 1:8. Additionally, in some embodiments of this application, the polymerization reaction temperature is 60°C to 80°C, and the reaction time is 4 to 8 hours.
[0067] The following examples illustrate the preparation of the modified polyurethane in this application. It should be noted that the following examples are not intended to limit the modified polyurethane of this application. Those skilled in the art can adjust the raw materials and preparation steps according to actual needs, as long as the modified polyurethane of this application can be obtained.
[0068] raw material: Hydrophilic monomers: Lithium 2,4-diaminobenzenesulfonate (DABS-Li), purity ≥99%; Lithium 5-sulfoisophthalate monoethylenediamine salt (SIPE-Li), purity ≥98%.
[0069] Polyester polyols: Polytetrahydrofuran ether diol (PTMG, Mn=1000), dehydrated under reduced pressure at 100℃ for 2 hours before use. Polycaprolactone diol (PCL, Mn=2000), dehydrated under reduced pressure at 80℃ for 2 hours before use.
[0070] Polyisocyanate: Isophorone diisocyanate (IPDI), purity ≥99.5%.
[0071] Catalysts and chain extenders: Dibutyltin dilaurate (DBTDL), analytical grade; 1,4-Butanediol (BDO), analytical grade, used as a chain extender.
[0072] Solvents and media: N,N-Dimethylformamide (DMF), anhydrous grade, used as a solvent in the oil phase. Deionized water (resistivity ≥18.2 MΩ·cm), used as a solvent in the aqueous phase. Acetone, analytical grade, used for viscosity adjustment and cleaning.
[0073] Coating and Modification Auxiliary Materials: Dispersant: Hydroxyethyl cellulose (HEC, viscosity 4000 mPa·s~6000 mPa·s), used to adjust the rheological properties of the coating solution. Wetting agent: Polyether-modified polysiloxane (nonionic), used to improve the spreadability of the coating solution on the PP membrane surface. pH adjuster: Ammonia solution (25 wt%), used to adjust the pH value of the aqueous phase.
[0074] Preparation steps: To obtain the oil phase: Under dry nitrogen protection, metered amounts of PTMG, PCL, and IPDI were added to a three-necked flask containing DMF, controlling the NCO / OH molar ratio to be 2.2:1. A small amount of DBTDL (approximately 0.05% of the total mass) was added, and the mixture was reacted at 75°C for 2.5 hours to obtain a DMF solution of polyurethane prepolymer (Pre-PU) with -NCO terminal groups.
[0075] Obtaining the aqueous phase: In another container, dissolve measured amounts of DABS-Li and SIPE-Li in deionized water, add measured amounts of BDO, and adjust the pH to 8-9 with ammonia to form a homogeneous aqueous phase. In this step, the molar ratio of lithium sulfonate groups to lithium carboxyl groups in the modified polyurethane product can be controlled by adjusting the molar ratio of the hydrophilic monomers corresponding to lithium sulfonate and lithium carboxyl groups. The hydrophilic monomer corresponding to lithium sulfonate is DABS-Li, and the hydrophilic monomer corresponding to lithium carboxyl is SIPE-Li. In this step, the benzene rings in DABS-Li and SIPE-Li are the linking groups.
[0076] Preparation of modified polyurethane: Under high-speed shear (8000 rpm), the oil phase was slowly added dropwise to the aqueous phase, controlling the mass ratio of oil phase to aqueous phase to be 1:5. After the addition was complete, the mixture was transferred to a 60℃ water bath and stirred at medium speed (500 rpm) for 4 hours. In this step, the -NCO groups at the end of the Pre-PU undergo interfacial polycondensation with the amine groups (from DABS-Li, SIPE-Li) and hydroxyl groups of BDO in the aqueous phase. At the same time, the lithium sulfonate and lithium carboxyl groups in the molecular chain endow the product with strong hydrophilicity, enabling the modified polyurethane to self-assemble in situ in the aqueous phase to form uniformly sized particles with a core-shell structure. In addition, the functionality of the modified polyurethane can be controlled by adjusting the amount of aqueous phase used in this step. Specifically, when the molar ratio of polyurethane prepolymer to hydrophilic monomer is 1:4, the functionality is 4; when the molar ratio is 1:6, the functionality is 6, and so on. The amount of hydrophilic monomer can be calculated based on mass and amount of substance, which will not be elaborated here.
[0077] After the reaction, post-processing can be performed. Specifically, the resulting milky white dispersion is subjected to vacuum distillation at 40°C to remove part of the solvent, yielding a modified polyurethane stabilized aqueous dispersion with a solid content of approximately 8 wt%. Dynamic light scattering (DLS) characterization shows an average particle size of approximately 85 nm and a polydispersity index (PDI) of 0.12.
[0078] After obtaining the modified polyurethane, the modified polyurethane aqueous dispersion is usually mixed and stirred with wetting agents, dispersants, etc., to obtain a modified slurry with a suitable viscosity. As an example, this application also provides a process for preparing the modified slurry. It should be noted that the modified slurry preparation process of this application should not be construed as limiting the modified slurry of this application. Those skilled in the art can adjust the raw materials and preparation steps according to actual needs.
[0079] Preparation of modified slurry: Take the above modified polyurethane aqueous dispersion, add 0.5% of wetting agent and 0.8% of HEC by mass, and stir magnetically at 200 rpm for 6 hours at room temperature to obtain a uniform and viscous coating slurry.
[0080] After obtaining the modified slurry with modified polyurethane, a diaphragm is prepared using the modified slurry. Therefore, the following steps are also involved: S200. The modified slurry is applied to at least one surface of the base membrane layer and cured to obtain a diaphragm.
[0081] This step can employ an aqueous dispersion coating method to modify the surface of the base membrane layer. In the process of preparing the separator, the surface of the base membrane layer is generally pretreated before the modified slurry is applied, followed by curing. As an example, the preparation process of the separator in this application is as follows: Pretreatment: The dried PE film is fixed on the base of the flatbed coating machine, and the surface of the PE film is treated with a corona treatment instrument (power 100W, speed 2m / min) to improve its surface energy.
[0082] Coating and molding: The prepared modified slurry is evenly coated onto the corona-treated PE film surface using a doctor blade coater, and the wet film thickness is set to 100μm.
[0083] Curing: The coated wet film is immediately transferred to a forced-air drying oven and pre-dried at 50°C for 30 minutes to remove most of the moisture. Then, it is heat-treated at 85°C for 1 hour to promote further interaction between the modified polyurethanes and between the modified polyurethanes and the surface of the base film layer, forming a stable membrane.
[0084] After the heat-treated diaphragm is removed and allowed to cool naturally to room temperature, the coating thickness can be measured using a thickness gauge, and then it can be punched into the required diameter and shape using a punching machine for later use. In the final diaphragm, the surface coating (i.e., the coating containing modified polyurethane) is approximately 3 μm thick, and the surface is uniform and dense.
[0085] S300. Obtain a battery cell assembly, which includes a negative electrode, a separator, and a positive electrode stacked together.
[0086] This step involves forming a battery cell assembly using the positive and negative electrodes and the aforementioned separator. It should be noted that the "stacked arrangement" in this step can refer to either stacking the negative electrode, separator, and positive electrode and then winding them to form a battery cell assembly, or stacking wafers to obtain a battery cell assembly; this application does not have any particular requirements in this regard.
[0087] S400: The cell assembly is placed inside the housing to obtain a single battery cell.
[0088] In this step, an electrolyte is also placed inside the casing, which will subsequently wet the battery cell assembly. Afterwards, to ensure the normal operation of the individual battery cells, a formation treatment is performed. Since the processes of wetting and formation treatment are relatively well-established, they will not be described in detail here; those skilled in the art can adjust them according to actual needs.
[0089] This application also provides a battery device, which includes the aforementioned battery cell, or a battery cell prepared by the aforementioned method. The battery device of this application can take the form of one or more of the following: battery module, battery pack, and energy storage battery.
[0090] Specifically, such as Figures 2-3 As shown, the battery device 100 includes a housing 10 and battery cells 20, with the battery cells 20 housed within the housing 10. The housing 10 provides space for the battery cells 20, and the housing 10 can have various structures.
[0091] In some embodiments, the housing 10 may include a first portion 11 and a second portion 12, which overlap each other, and together define a receiving space for accommodating the battery cell 20. The second portion 12 may be a hollow structure with one open end, and the first portion 11 may be a plate-like structure, with the first portion 11 covering the open side of the second portion 12 so that the first portion 11 and the second portion 12 together define the receiving space. Figure 3 As shown. The first part 11 and the second part 12 can both be hollow structures with an opening on one side, with the opening side of the first part 11 covering the opening side of the second part 12. Of course, the box 10 formed by the first part 11 and the second part 12 can be of various shapes, such as a cylinder, a cuboid, etc.
[0092] In the battery device 100, the battery cell 20 can be a single cell or multiple cells. Multiple battery cells 20 can be connected in series, parallel, or a combination thereof. A combination thereof means that multiple battery cells 20 are connected in both series and parallel configurations. Multiple battery cells 20 can be directly connected in series, parallel, or a combination thereof to form a whole, which is then housed within the housing 10. Alternatively, the battery device 100 can also consist of multiple battery cells 20 first connected in series, parallel, or a combination thereof to form battery modules, which are then connected in series, parallel, or a combination thereof to form a whole, which is also housed within the housing 10.
[0093] The battery device 100 may also include other structures, for example, the battery device 100 may also include a busbar for realizing electrical connection between multiple battery cells 20.
[0094] This application also provides an energy storage device, including the aforementioned battery device, wherein the battery device is used to store electrical energy. The energy storage device of this application is not limited to, but is also including, residential energy storage cabinets, commercial energy storage cabinets, energy storage containers, energy storage racks, energy storage power stations, energy storage battery packs, or portable energy storage systems. The energy storage device may also include an energy management system (EMS), a battery management system (BMS), and a power conversion system (PCS).
[0095] This application also provides an electrical device, including the aforementioned battery device, wherein the battery device is used to provide electrical energy. The electrical devices of this application include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0096] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0097] Example 1 This embodiment provides a battery cell, including a cell assembly, a casing, and an electrolyte. The cell assembly and electrolyte are located inside the casing. The cell assembly includes a negative electrode, a separator, and a positive electrode stacked together. The separator includes a base film layer, and both surfaces of the base film layer are provided with modified polyurethane. The main link of the modified polyurethane is a branched organolithium group, which includes lithium sulfonate groups and lithium carboxyl groups.
[0098] The electrolyte contains ethylene carbonate, propylene carbonate, and dimethyl carbonate as solvents, and lithium salt is lithium hexafluorophosphate.
[0099] In the negative electrode, the active material is graphite; in the positive electrode, the active material is lithium iron phosphate.
[0100] The modified polyurethane content in the diaphragm is 3 g / m³. 2 In the modified polyurethane, the molar ratio of lithium sulfonate groups to lithium carboxyl groups is 1:1, and the functionality of the organolithium is 4.
[0101] Examples 2 to 5 Compared to Example 1, the main difference is that the content of modified polyurethane in the diaphragm is adjusted, as shown in Table 1.
[0102] Examples 6 to 9 Compared to Example 1, the main difference is that the molar ratio of lithium sulfonate groups to lithium carboxyl groups in the modified polyurethane is adjusted, as shown in Table 1.
[0103] Examples 10-12 Compared to Example 1, the main difference lies in adjusting the functionality of the organolithium in the modified polyurethane, as shown in Table 1.
[0104] Comparative Example 1 This comparative example provides a battery cell, which differs from Example 1 mainly in that the separator is a currently available commercial PE separator. The surface of this separator does not contain modified polyurethane.
[0105] Comparative Example 2 This comparative example provides a battery cell, which differs from Example 1 mainly in that the two surfaces of the base film layer are made of polyurethane; the content of modified polyurethane in the separator is 3 g / m³. 2 .
[0106] Test methods and equipment Lithium-ion transport performance test of the diaphragm Asymmetric batteries were assembled using the separators from the examples and comparative examples, employing a constant potential polarization method combined with EIS testing: lithium metal sheet | separator | lithium metal sheet.
[0107] First, test the initial impedance (EIS, frequency range 1 Hz ~ 1 MHz) to obtain the initial interface resistance R0 and the initial current I0.
[0108] Then a small DC polarization voltage ΔV (10 mV) is applied, and the change of polarization current over time is recorded until the current stabilizes, thus obtaining the steady-state current Is (typically the polarization time is about 1~3 h).
[0109] After polarization, the EIS was tested again to obtain the polarized interface resistance Rs. The lithium-ion transference number was then calculated using the following formula:
[0110] Cyclic performance test The battery cells were charged at a constant current and constant voltage of 0.5C (CCCV, cutoff current 0.05C), and then discharged at a constant current of 0.5C for 1000 cycles to test the capacity retention of the battery cells.
[0111] Diaphragm heat shrinkage rate test The diaphragms from the examples and comparative examples were cut into 10 cm × 10 cm samples, and their original dimensions (length L0, width W0) were measured in an environment with a temperature of 25°C and humidity <30%. The samples were then placed in an oven and heated at 90°C, 120°C, and 150°C for 1 h, respectively. After cooling to room temperature, the dimensions (L, W) were measured again. The formula for calculating the heat shrinkage rate is as follows: Heat shrinkage rate (%) = (L0-L) / L0×100%.
[0112] Three parallel samples were tested at each temperature point, and the average value was taken.
[0113] The test results are shown in Table 1.
[0114] Table 1
[0115] As can be seen from the above, the separator in this application embodiment has good ion transport performance. Therefore, compared with the prior art Comparative Example 1, the separator in this application embodiment has better ion transport performance, and the cycle performance and safety performance of the battery cell are better. In particular, as can be seen from Examples 1 to 5, when the content of modified polyurethane in the separator is 1 g / m³, 2 ~5g / m 2 When the modified polyurethane content is increased to 5.2 g / m³, the battery's cycle performance and safety performance are better; and as shown in Example 5, although the modified polyurethane content is increased to 5.2 g / m³, the battery's cycle performance and safety performance are better. 2 Afterwards, the ion transport performance of the separator remains high, but it affects wetting and bonding strength, leading to a significant decrease in the cycle performance and safety performance of the battery cell compared to Example 1. Specifically, as shown in Examples 1 and 6-9, when the molar ratio of lithium sulfonate groups to lithium carboxyl groups in the modified polyurethane is 1:1 to 3:1, the cycle performance and safety performance of the battery cell are better. Specifically, as shown in Examples 1 and 10-12, when the functionality of the modified polyurethane is 4-6, the cycle performance and safety performance of the battery cell are better; and as shown in Example 12, although the separator still has good lithium-ion transport performance after the functionality increases to 8, considering other factors, the cycle performance and safety performance of the battery cell are significantly lower than in Example 1.
[0116] Furthermore, as can be seen from Example 1 and Comparative Example 1, simply using polyurethane to modify the base film layer can actually lead to a further decrease in the cycle performance and safety performance of the battery cells.
[0117] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.
Claims
1. A battery cell, characterized in that, include: A battery cell assembly, the battery cell assembly comprising a negative electrode, a separator and a positive electrode stacked together; The housing, in which the battery cell assembly is located; Electrolyte, wherein the electrolyte is located within the housing; The diaphragm includes a base membrane layer, at least one surface of which is provided with modified polyurethane, wherein the main link of the modified polyurethane is a branched organolithium group, and the organolithium group includes lithium sulfonate group and lithium carboxyl group. The modified polyurethane has a core-shell structure, wherein the core of the modified polyurethane includes the main chain, and the shell of the modified polyurethane includes the organolithium group; a connecting group is disposed between the core and the shell. The modified polyurethane is formed by polymerizing a polyurethane prepolymer and a hydrophilic monomer, wherein the hydrophilic monomer provides the organolithium group, and the linking group is formed after the hydrophilic monomer and the polyurethane prepolymer are polymerized.
2. The battery cell according to claim 1, characterized in that, The linking group includes a first group and a second group, wherein the first group is connected to the main chain of the modified polyurethane, and the second group is connected to the first group and the organolithium group respectively; the first group includes an amide bond, and the second group includes an aromatic group, wherein the aromatic group includes at least one of phenyl, naphthyl, biphenyl, pyridyl or pyrimidinyl.
3. The battery cell according to claim 1, characterized in that, The molar ratio of the lithium sulfonate group to the lithium carboxyl group is 1:1 to 3:
1.
4. The battery cell according to any one of claims 1 to 3, characterized in that, In the modified polyurethane, the functionality of the organolithium group is 4 to 6.
5. The battery cell according to claim 1, characterized in that, The number average molecular weight of the modified polyurethane is 5,000 to 200,000.
6. The battery cell according to claim 1, characterized in that, The modified polyurethane content in the diaphragm is 1 g / m³. 2 ~5g / m 2 .
7. A method for preparing a battery cell according to any one of claims 1 to 6, characterized in that, include: A modified slurry is obtained, the modified slurry comprising modified polyurethane, wherein the main link of the modified polyurethane is an organolithium group, and the organolithium group comprises lithium sulfonate group and lithium carboxyl group. The modified slurry is coated onto at least one surface of the base film layer, and the modified slurry is cured to obtain a diaphragm; A battery cell assembly is obtained, the battery cell assembly comprising a negative electrode, the separator, and a positive electrode stacked together; The cell assembly is placed inside the housing to obtain a single battery cell.
8. The method for preparing a battery cell according to claim 7, characterized in that, The preparation steps of the modified polyurethane include: An oil phase is obtained, wherein the oil phase comprises a polyurethane prepolymer; An aqueous phase is obtained, the aqueous phase comprising a hydrophilic monomer and a chain extender, the hydrophilic monomer comprising lithium sulfonate salt and lithium carboxyl salt, and the hydrophilic monomer containing a polymeric group; The oil phase and the aqueous phase are mixed and subjected to a polymerization reaction to obtain the modified polyurethane.
9. The method for preparing a battery cell according to claim 8, characterized in that, During the polymerization reaction, the mass ratio of the oil phase to the water phase is 1:2 to 1:
8.
10. The method for preparing a single battery cell according to claim 8, characterized in that, The polymerization reaction is carried out at a temperature of 60℃ to 80℃ for a reaction time of 4h to 8h.
11. A battery device, characterized in that, The battery device includes a battery cell as described in any one of claims 1 to 6, or a battery cell prepared by the method described in any one of claims 7 to 10, and the battery device includes one or more of a battery module, a battery pack, or a battery cluster.
12. An energy storage device, characterized in that, Includes the battery device as described in claim 11, wherein the battery device is used to store electrical energy.
Citation Information
Patent Citations
Method for preparing sulfoacid / carboxylic acid waterborne polyurethane
CN102653585A
Diaphragm and battery
CN115986311A
Secondary battery and preparation method thereof, energy storage system and electric equipment
CN120341505A